A novel bioenergy feedstock in Latin America? Cultivation potential of Acrocomia aculeata under current and future climate conditions. (August 2016) - Plath, Mirco; Moser, Christine; Bailis, Rob; Brandt, Patric; Hirsch, Heidi; Klein, Alexandra-Maria; Walmsley, David; von Wehrden, Henrik
Abstract: Plant oil is a key commodity in the global economy, particularly for food and bioenergy markets. However, current production practices often impair smallholder livelihoods, cause land use changes, and compete for food production. The neotropical palm Acrocomia aculeata is currently being promoted as a novel sustainable biomass feedstock, particularly for bioenergy, but only little is known about the palm's ecological requirements. Based on a comprehensive literature and database search for recorded occurrences of A. aculeata in Latin America, we computed an ecological niche modeling to determine the palm's potential distribution area based on climatic and soil variables. We subsequently considered current land cover and predicted future climate change scenarios to discuss the cultivation potential of A. aculeata within its possible distribution area. The results revealed a large potential to cultivate A. aculeata in Latin America under current abiotic environmental conditions. The two core distribution regions identified were (1) Central America including the Caribbean, northern Colombia and Venezuela, and (2) southern Brazil and eastern Paraguay. A considerable proportion of the medium to highly suitable growing areas were found to be currently used for agricultural production or covered by land types with high conservation and carbon sequestration value. Applying the model under the IPCC's A2A 'business as usual' emission scenario suggested that by 2080 the vast majority of suitable growing areas severely decline in extent or disappear entirely. Our ecological niche modeling thus shows that despite the palm's high cultivation potential, a sustainable deployment of A. aculeata requires a precautious, evidence-based approach. Highlights: Acrocomia aculeata is currently promoted as novel sustainable biomass feedstock. Our ecological niche modeling revealed a high cultivation potential for this palm in Latin America. Yet, a crucial proportion of the predicted areas were located in areas of high conservational value. Also, climate change scenarios predicted a substantial prospective reduction of suitable areas. A sustainable deployment of A. aculeata requires a precautious, evidence-based approach.